Effect of Dopant Concentration on the Structural, Optical and Sensing Properties of (SnO2)1-x(TiO2:CuO)x Sprayed Films - Mahmood et al. (مجلة بغداد للعلوم, 2019)
Spray pyrolysis technique was subjected to synthesized (SnO2)1-x (TiO2: CuO) x Thin films on different substrates like glass and single crystal silicon using. The structure of the deposited films was studied using x-ray diffraction. A more pronounced diffraction peaks of SnO2 while no peaks of (CuO , TiO2 ) phase appear in the X-ray profiles by increasing of the content of (TiO2 , CuO) in the sprayed films. Mixing concentration (TiO2 , CuO) influences on the size of the crystallites of the SnO2 films ,the size of crystallites of the spray paralyzed oxide films change in regular manner by increasing of (TiO2 , CuO) amount. The effect of mixing concentration on the optical properties of the films was also investigated. The reflectance and transmittance spectra  in the wavelength range (300-1100) nm were employed to determine the optical properties such as energy band gap (Eg) and refractive index (n),  extinction coefficient  (k) , real and imaginary parts of dielectric constants (ε1, ε2) for (SnO2)1-x(TiO2:CuO)x films. The energy band gap omit of which showed reduction from (3.65 to 2.2) eV by reducing of SnO2 amount from (100 to 70) % .The reduction of energy band gap was ascribed to the new tail states introduced in the band gap of tin oxide. The sensitivity of the prepared sensor film was determined resistance difference of the films when exposed to oxidizing gas. The data declared that the mixed SnO2 films have better sensitivity in comparison with unmixed films.